Epigenetic programming of the germ line: effects of endocrine disruptors on the development of transgenerational disease - Anway, Matthew D (Reprod Biomed Online, 2008)
Epigenetic programming of the germ line occurs during embryonic development in a sex-specific manner. The male germ line becomes imprinted following sex determination. Environmental influences can alter this epigenetic programming and affect not only the developing offspring, but also potentially subsequent generations. Exposure to an endocrine disruptor (i.e. vinclozolin) during embryonic gonadal sex determination can alter the male germ-line epigenetics (e.g. DNA methylation). The epigenetic mechanism involves the alteration of DNA methylation in the germ line that appears to transmit transgenerational adult onset disease, including spermatogenic defects, prostate disease, kidney disease and cancer.